Crowd location forecasting at points of interest. (2015) - AlvarezLozano, Jorge; GarcíaMacías, J. Antonio; Chávez, Edgar
Predicting the location of a mobile user in the near future can be used for a large number of usercentred ubiquitous applications. This can be extended to crowdcentred applications if a large number of users is included. In this paper we present a spatiotemporal prediction approach to forecast user location in a mediumterm period. Our approach is based on the hypothesis that users exhibit a different mobility pattern for each day of the week. Once factored out this weekly pattern, user mobility among points of interest is postulated to be markovian. We trained a hidden Markov model to forecast user mobility and evaluated our approach using a public dataset. The experimental results show that our approach is effective considering a time period of up to 7 h. We obtained an accuracy of up to 81.75% for a period of 30 min, and 66.25% considering 7 h.